Perancangan Kampanye Sosial Tentang Kepedulian Terhadap Organ Reproduksi untuk Pelajar SMA - Dena Pasha (Wimba : Jurnal Komunikasi Visual, 2021)
High school students are at the perfect age in providing material on how to care for the health of reproductive organs because they are still being monitored by teachers and parents. Due to a lack of understanding and concern for the function and health of the reproductive organs, teenagers in Indonesia contribute to the number of STI sufferers. Therefore, this social campaign is packaged into something that can be considered not taboo for high school students to learn, can be a means for teachers to educate their students. This campaign is expected to increase high school students' awareness of the reproductive organs which are very important organs in carrying out their lives as human beings without giving the impression of being taboo.